Analisis kemampuan berpikir kritis siswa kelas XI SMAN 4 Pekanbaru pada pembelajaran Biologi TA 2020/2021 - Nurkhairo Hidayati; Leni Indriana (Biology and Education Journal, 2022)
This study aims to determine the critical thinking skills student of class XI SMAN 4 Pekanbaru in learning biology TA.2020/2021. This research is quantitative descriptive. The instrument that is used is a matter of critical thinking, observasion, interviews, and questionnaires. Data collection is carried March 2021. The samples were used in the research of student class XI IPA 1 to XI IPA 6 totaling 78 students. The results showed that the highest critical thinking indicators were strategy and tactics indicators with a percentage of 97% (very high category). The indicator that occupies the lowest score is the indicator that provides further explanation with a percentage of 50% (low category). Other indicators have different percentages, namely the indicator giving a simple explanation gets a percentage of 96% (very high category), followed by a conclusion indicator with a percentage of 72% (low category), and an indicator of building basic skills with a percentage of 65% (low category). Based on the results of research conducted on students' critical thinking abilities on excretory system material, it can be concluded that students' critical thinking abilities are in the medium category with a percentage of 76%.